Women’s Political Representation in the Czech Republic in the context of the transition from Communism to Democracy - Gelnarová, Jitka; Fousková, Marie V. (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
This paper gives an overview of women’s political representation in Czechoslovakia and the Czech Republic after the fall of the iron curtain, framed in the context of the transition from Communism to democracy. It is concerned with both continuity and discontinuity between the old and the new regime regarding the political engagement of women – the persistence of traditional family model and gender stereotypes on one hand, and the radically changed roles of the private and the public sphere on the other. It focuses on the mechanisms disadvantaging women in their access to political power and on public attitudes to the measures which could level the playing field, namely gender quotas for political party candidate lists.

W artykule przedstawiony został przegląd reprezentacji politycznej kobiet w Czechosłowacji oraz w Czechach po upadku żelaznej kurtyny, w kontekście przejścia od systemu komunistycznego do demokracji. Artykuł obejmuje rozważania zarówno dotyczące ciągłości i zmiany, pomiędzy starym a nowym systemem, skupiając uwagę na zaangażowaniu politycznym kobiet – począwszy od utrzymywania tradycyjnego modelu rodziny i stereotypów płciowych, a kończąc na radykalnych zmianach ról w sferze prywatnej i publicznej. Koncentrując się na mechanizmach blokujących kobiety w ich dostępie do władzy politycznej i postawach społecznych, które mogłyby wyrównać ostatecznie szanse, a mianowicie zastosowaniu parytetów płciowych na listach wyborczych partii politycznych.
Reprezentacja polityczna kobiet w Republice Czeskiej, w kontekście przejścia od komunizmu do demokracji
Keywords: women; political participation; gender; quotas; elections; Czech Republic; Communism; kobiety; partycypacja polityczna; gender; parytety; wybory; komunizm; Republika Czeska Article